Confucian Historical Narratives and Misogynic Culture in South Korea - Bernadine Grace Alvania Manek (Journal of Asian Social Science Research, 2023)
President Yoon Suk-yeol's campaign for the presidency embraces the anti-feminism movement that has further fueled the misogynistic culture in South Korea. South Korea is quite thick with patriarchy and misogyny because there is a lot of criticism of women, especially feminists. This article analyses the phenomenon of misogynistic culture in South Korea using document-based research and internet-based research techniques. It employs Foucault's discourse of power and the concept of misogyny to analyse the impact of history on misogynist culture in contemporary South Korea. The findings show that as Confucian teachings are the basis of state ideology in South Korea, Korean society believes in the chastity of women. In the Koran history, a negative connotation was given to women who are considered to have damaged the country’s ‘Joseon-ness’ and the standard of femininity in South Korean society. Given South Korea's high level of sexism and low level of female empowerment, the representation of males in dramas as caring and empathetic is unfortunately not representative of the real world. Sexist behaviour in South Korea is founded on Confucian ideology.